Manfaat Hutan Mangrove dalam Kehidupan Masyarakat di Kelurahan Guraping Kecamatan Oba Kabupaten Tidore Kepulauan - Darling Surya Alnursa (Peneliti.net, 2023)
Mangrove forest is one of the natural wealth contained in nature from the many natural resources found in our country, Indonesia. Therefore the potential of Natural Resources contained in Mangrove Forests has a high value of benefits for the sustainability of the local Ecosystem, the surrounding community in meeting the needs of life and broadly for the Government and the State. As a multi-beneficial Natural Resource, Mangrove Forests have a large contribution to the State in order to achieve the State's goals, namely the welfare of the community. The benefits of mangrove forests are divided into two parts, namely ecological benefits and economic benefits. Its ecological benefits include being able to withstand abrasion and erosion due to raging waves, being able to withstand raging winds, as a breeding ground for marine organisms, and as a provider of nutrition for marine biota. Its economic benefit or function is that it can be used as a tourism spot, and animals and plants found in mangrove forests can be used to meet the needs of people's lives. This research was conducted in Guraping Village, Oba District, Tidore Islands City with the aim of knowing the benefits of mangrove forests for people's lives in meeting their daily needs. The research method used is survey method with this type of research is qualitative. The results of this study indicate that the benefits of natural resources contained in mangrove forests have the potential to be used to meet the needs of people's lives. Based on the results and discussion, the conclusion that can be drawn is that the natural resources of mangrove forests are very beneficial for people's lives, especially those who live in areas around mangroves.